Integrating Biodiversity and Livelihood Protection in Mining Operations in Garcia-Hernandez, Bohol - Desucatan, Jose Villaceran; Acenas, Angelo A.; Polinar, Mark Anthony N. (Future Science / FSH-PH Publications, 2024)
Mining operations pose a significant threat to biodiversity and the livelihood of community people. Residents living near the mining sites must adjust to the changes brought about by the onset of mining activity, especially with their lost livelihood. Mining companies must provide alternative livelihood for residents to ensure sustainability. However, some livelihoods are not aligned with the Department of Environment and Natural Resources Administrative Order 2022-004. This study assessed the alignment of livelihood projects, reasons for not passing the Biodiversity Friendly Enterprise (BDFE) index, and suggested livelihood projects. The questionnaire gathered items indicated from the administrative order as a standard for passing the said index. The result revealed that most livelihood projects do not conform to the administrative order. The most glaring issues are the financial constraints and insufficient information about the BDFE index. Proposed livelihood projects on Traditional Hilot and Cacao Production proved to be highly supported in preserving traditional practices and furthering agricultural industries. Enhancing our capacity, improving project planning processes, and incorporating community feedback into livelihood projects to achieve better outcomes is essential. This will increase compliance with the DAO guidelines and promote sustainable community development. Additionally, these findings have implications for better adoption of the BDFE Index, as it is crucial to provide enhanced information and address financial constraints.